Field efficiency for infield oil palm Fresh Fruit Bunch (FFB) collection operation / Fauzan Harith Izat Farizan - Farizan, Fauzan Harith Izat (Faculty of Plantation and Agrotechnology, 2018)
Oil Palm (Elaeis guinensis) one of the biggest crop production in Malaysia as the source of income in the country. Labor are intensively being used in the operation of oil palm production and palm oil is also exported to the demanded country around the globe. Foreign labor from neighboring country especially Indonesia have the highest number of labor in harvesting oil palm bunches. As the development of oil palm plantation growth for the past few years in Indonesia, labor shortage in plantation has now becoming a serious issue in Malaysian plantation. There are more and more foreign labor that willing to return to their homeland to work at their plantation area in their country. As a result, grabber machine has been starting to be implemented in developed company to replace labor work in infield FFB collection. Many machine are produced by researchers to help in plantation operation. Tractor grabber machine is one of the most effective machine that suitable to be used in collection of FFB in the field. The field efficiency of the grabber machine is important to be measured to examine whether the machine is efficient enough to be used in plantation to replace human workforce. At Merlimau six operators are observed in their efficiency in operating six grabber machine with the same model. As a result, the average field efficiency of the machine is at 91% which is considered as highly efficient in machinery range. Company are recommended to hire operator with higher experiences, which tend to have higher field efficiency.